The Role of before Marriage Relationships in Mrraiage Difficulties - Elaheh Nejhadkarim; Tahereh Saeidifard; Narges Vahidnia; Khodabakhsh Ahmadi (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Emotional difficulties are a serious threat to the family and marriage outside of his normal route and marriage violated. The purpose of this study, the role of infidelity in men and women had premarital relationships. Materials and Methods: The study was a correlation method, the population included men and married women in Tehran that 345 patients (170 males and 175 females) were selected using stratified sampling, for example. Record pre-marital relationships and infidelity to help self-report questions were asked. To analyze the data, chi-square method was used. Results: The analysis showed that a history of premarital relations with emotional infidelity (P<0.001, χ2=69.3), betrayal, physical (P<0.001, χ2=15. 8), and sexual infidelity (P<0.001, χ2=14.6) is a statistically significant relationship. Conclusion: The results showed that the relationship of marriage in later life is likely to lead to marital infidelity. The results of this study can help the pathology and prevention of marital infidelity.